Peran Majelis Taklim Mingguan dalam Memperkuat Pemahaman Keagamaan : (Studi Kasus: Majelis Taklim Nurul Iman Bambu Apus Pamulang) - Sabrina Syayla Putri; Syaripulloh Syaripulloh (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Majelis Taklim is a tradition of learning among the people of Indonesia, both rural and urban, the tradition of learning is still going on today. The purpose of the study was to describe the role of the weekly taklim assembly in strengthening the religious understanding of housewives held every Saturday morning in Bambu Apus Village, Pamulang District, South Tangerang City. In this research, the method used is qualitative because the data obtained is processed and explained in the description of the author. In obtaining data, the author used observation, interview and documentation methods. The data sources in this study include primary data sources in the form of interviews with material speakers, administrators and a congregation of Majelis Taklim Nurul Iman, as well as secondary data sources derived from documentation of activities. The results of the study concluded that the role of Majelis taklim Nurul Iman included, among others, fixing the reading of short surahs, apart from being a place to learn religion as well as improving the household economy, there was an economic turnover because the Saturday morning taklim assembly was attended by people from various social layers, strengthening religious understanding, and fostering harmony between communities with silaturrahim.